Pengaruh Kegiatan Forum Annisa Terhadap Pembentukan Akhlak Muslimah - Sulaiman, Sulaiman; Anggraini, Ridha Angesti (An-Nuha, 2025)
This study analyzes the influence of Annisa Forum activities on the development of Muslimah morality at SMP Negeri 1 Pasaman. Employing a quantitative correlational approach, the research involved 30 active members of the Annisa Forum from grades VII and VIII. Data were collected via questionnaires, observations, and documentation, then analyzed using descriptive statistics, assumption tests, and simple linear regression. Results indicate that the Annisa Forum has a positive and significant influence of 69.8% on Muslimah morality, with a correlation coefficient (r=0.835) suggesting that increased student activity correlates with higher moral quality. The remaining 31.3% of the variation is attributed to other factors. The regression constant (31.72) denotes a baseline morality level even without forum participation, referencing the concept of fitrah. Conclusively, the Annisa Forum proves an effective medium for social interaction, Islamic values internalization, and character development, underscoring the role of learning environments in shaping morals according to Islamic teachings.